Level of extra and intracellular enzymes during preservation of good and poor quality ejaculates in crossbred bulls - GEBRESELASSIE, G A; SRIVASTAVA, S K; GHOSH, S K; TRIPATHI, R P (The Indian Journal of Animal Sciences, 2013)
Activities of superoxide dismutase (SOD), catalase (CAT) as extracellular and glutamate pyruvate transaminase (GPT), lactic dehydrogenase (LDH) as well as glutamate oxaloacetate transaminase (GOT) as intracellular enzyme were estimated in seminal plasma of good and poor quality ejaculates of crossbred bull semen. SOD, LDH and GOT activities differed significantly in both types of ejaculates at pre-freeze and post- thaw levels, whereas no difference was observed in catalase activity. The GPT activity was also higher in seminal plasma at post-thaw than prefreeze level in both types of ejaculates but it was less compared to other enzymes. Although there was loss in SOD activity during freezing thawing in both type of ejaculates but it was more in poor quality (62.5%) than good quality (50.4%), which may be due to the higher percentage of dead spermatozoa during freeze thaw in former than later. LDH and GOT enzyme activity also increased in seminal plasma in both types of ejaculates after post-thaw but it was higher in poor quality, which indicated that damage in sperm plasma membrane was more in poor quality during freezing thawing.